2018
DOI: 10.3389/fpsyg.2017.02207
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Detect Deception from Evasive Answers and Inconsistencies across Repeated Interviews: A Study with Lay Respondents and Police Officers

Abstract: Previous research has shown that inconsistencies across repeated interviews do not indicate deception because liars deliberately tend to repeat the same story. However, when a strategic interview approach that makes it difficult for liars to use the repeat strategy is used, both consistency and evasive answers differ significantly between truth tellers and liars, and statistical software (binary logistic regression analyses) can reach high classification rates (Masip et al., 2016b). Yet, if the interview proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
(115 reference statements)
0
9
1
Order By: Relevance
“…The consistency heuristic is used to inform veracity judgements when examining multiple interviewees' statements (Strömwall, Granhag, & Jonsson, 2003), when examining the consistency within statements (Reinhard, Greifeneder, & Scharmach, 2013), and when comparing interviewee statements to evidence (Hartwig, Granhag, Strömwall, & Vrij, 2005). The consistency heuristic has been mostly examined in relation to multiple statements taken from the same individual (Granhag & Strömwall, 2000; Masip et al, 2018; Strömwall & Granhag, 2003). To date there is little research examining whether people actually use the consistency heuristic when making veracity judgements across multiple statements, or whether they simply report it as a perceived cue to deception.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The consistency heuristic is used to inform veracity judgements when examining multiple interviewees' statements (Strömwall, Granhag, & Jonsson, 2003), when examining the consistency within statements (Reinhard, Greifeneder, & Scharmach, 2013), and when comparing interviewee statements to evidence (Hartwig, Granhag, Strömwall, & Vrij, 2005). The consistency heuristic has been mostly examined in relation to multiple statements taken from the same individual (Granhag & Strömwall, 2000; Masip et al, 2018; Strömwall & Granhag, 2003). To date there is little research examining whether people actually use the consistency heuristic when making veracity judgements across multiple statements, or whether they simply report it as a perceived cue to deception.…”
mentioning
confidence: 99%
“…One of the most commonly reported verbal cues to deception is between‐statement (in)consistency (Granhag & Strömwall, 2000, 2001); reported by both laypeople (Krix, Sauerland, Lorei, & Rispens, 2015) and legal professionals (Strömwall & Granhag, 2003). When examining the perceptions of the deception‐consistency relationship amongst uninformed laypeople and investigators, Masip et al (2018) found that uninformed laypeople who were asked to make veracity judgements on a series of written statements most commonly reported (90%) utilising (in)consistency to assist in making their judgement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With research indicating that truth tellers report more details than liars (Amado et al, 2016; DePaulo et al, 2003), it was predicted that truth tellers would include significantly more repetitions in their subsequent interview than liars, particularly if they initially completed the SAI, as they would have initially reported more details which they could repeat (Hypothesis 3). It was also predicted that as reminiscences are commonly found in repeated honest recalls (Fisher et al, 2009; Gilbert & Fisher, 2018; Strange et al, 2014), truth tellers will include significantly more reminiscences in their subsequent interview than liars, who may avoid including new information, as they wish to be perceived as consistent (Granhag & Strömwall, 1999), particularly if they initially completed the SAI (Hypothesis 4). Liars may feel that by completing the SAI, they have already provided an adequately detailed account and be reluctant to expand their statement further, in an effort to keep their story simple (Granhag & Strömwall, 2002; Hartwig, Granhag & Strömwall, 2007).…”
Section: The Self‐administered Interviewmentioning
confidence: 99%
“…Granhag et al (2016) also found that the consistency of truth tellers and liars was similar when examining repetitions, reminiscences and omissions. Yet when Masip et al (2018) asked uninformed laypeople to make veracity judgements on a series of written statements, they found that 90% of the laypeople reported using consistency/inconsistency to assist in making their judgement. This is incongruous with research examining truth tellers' and liars' consistency, as well as memory research, which suggests that some types of inconsistencies, such as omissions and reminiscence, are commonly found in memory accounts (Fisher, Brewer & Mitchell, 2009; Gilbert & Fisher, 2006; Strange, Dysart, & Loftus, 2014).…”
Section: Introductionmentioning
confidence: 99%